Analisis Harga Pokok Produksi Untuk Menentukan Harga Jual Tahu - Anis Khaerunnisa; Robert Pius Pardede (Institut Bisnis dan Informatika Kesatuan, 2021)
Determination of the cost of production is very important considering the benefits of information on the cost of production are to determine the selling price of the product, monitoring the realization of production costs, calculating the periodic income and determining the cost of inventories of finished products and products in process that will be presented in the balance sheet cost elements into the cost of production, there are two approaches, namely Full Costing and variable costing. Full Costingis a method of determining the cost of production that takes into account all elements of production costs into the cost of production consisting of raw material costs, direct labor costs, and factory overhead costs, both variable and fixed. While variable costing is a method of determining the cost of production consisting of raw material costs, direct labor costs, and variable factory overhead costs. This study aims to determine the analysis of the cost of production method applied to the compehu Home Industry and to find out the comparison of the calculation of the cost of production in determining the price of tofu juak in the compehu Home Industry. Keywords: Full Costing, Variable Costing, and Cost of Production.